Exploring frataxin function - Busi, María Victoria (2011)
Frataxin is a nuclear-encoded mitochondrial protein highly conserved in prokaryotes and eukaryotes. Its deficiency was initially described as the phenotype of Friedreich´s ataxia, an autosomal recessive disease in humans. Although several functions have been described for frataxin, that is, involvement in Fe-S cluster and heme synthesis, energy conversion and oxidative phosphorylation, iron handling and response to oxidative damage, its precise function remains unclear. Although there is a general consensus on the participation of frataxin in the maintenance of cellular iron homeostasis and in iron metabolism, this protein may have other specific functions in different tissues and organisms.